Operation Theater Sterilization and Modular Operation Theater - Richa Gupta; Prashant K. Bawankule (Delhi Journal of Ophthalmology)
Sterilization holds the most important role in ophthalmic practice. The slow but steady change in sterilization technique over the decades has revolutionized today’s ophthalmic surgery as well as its outcome. Here, in this article, we will discuss all the important aspects of sterilization in an ophthalmic operation theater (OT). We will also discuss the meaning, need, and peculiarities of a modular ophthalmic OT.